Structural studies of surface modified oil palm empty fruit bunch with alkaline pre-treatment as a potential filler for the green composite - Nur Athirah, Mohamad Radzi; Azizul Helmi, Sofian; Saidatul Shima, Jamari (Malaysian Tribology Society (MYTRIBOS), 2020)
A green composite consists of natural and recyclable materials has become one of the attractive topics in advanced material. The hydrophilic properties of oil palm empty fruit bunch (OPEFB) used in green composite is difficult to bind with hydrophobic polymer. Hence, the surface modification of this filler is required to increase its surface area and roughness for better adhesive purposed. In this research study, the ultrasonification method has been performed to treat the OPEFB fiber with alkaline pre-treatment (sodium hydroxide solution (NaOH)) by using different concentration (1,2,3,4 and 5 w/v%). Fourier Transform Infrared Spectroscopy (FTIR) and Scanning Electron Microscopy -Energy Dispersive X-Ray (SEM-EDX) were performed to characterize and determine the surface roughness, area and pore enlargement for the fillers. The 5w/v% of treated OPEFB fiber was found to impose a significant impact on increasing the surface roughness, area and pore enlargementof the fiber. This modified filler has a potential to improve the thermal, mechanical and adhesiveness properties with its matrix to make a good green composite.